PERAN PKPT IPNU-IPPNU UIN RADEN INTAN LAMPUNG DALAM MENANAMKAN INTEGRITAS MAHASISWA DI BIDANG KARYA ILMIAH - Daniel Irvansyah; Agus Pahrudin; Ida Faridatul Hasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The crisis of academic integrity in higher education has become a serious challenge in the digital era, marked by the rise of plagiarism, data fabrication, and publications in predatory journals. This study aims to describe the implementation of academic integrity values through the Scientific Literature Review (KALIL) program organized by the PKPT IPNU-IPPNU at UIN Raden Intan Lampung, as well as to identify its supporting and inhibiting factors. This research employs a qualitative descriptive approach using the case study method. Data were collected through in-depth interviews, participatory observation, and documentation studies, then analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results indicate that PKPT IPNU-IPPNU plays a significant role in instilling values of honesty and academic responsibility through KALIL activities oriented toward scientific writing training, discussions on academic ethics, and the habituation of proper citation. This program also contributes to improving students' scientific literacy and fostering a culture of academic integrity. The main supporting factors for the program's success include the high demand among students for scientific writing training and active support from advisors, while the inhibitors include fluctuating participant attendance, limited facilities, and inconsistency in scheduling. This research reaffirms that collaboration between student organizations and advisors plays a crucial role in building an honest, ethical, and sustainable academic ecosystem within the university environment.